Analisis Pragmatik dalam Kesantunan Tindak Tutur Tokoh pada Cerpen ‘Thank You, Ma’am’ Karya Langston Hughes - Alifah Zahra Adhiyana; Putri Fatimah Azzahra; Wafiq Aziz Wardah; Dadan Firdaus (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study analyzes the politeness strategies of characters' speech acts in Langston Hughes' short story "Thank You, Ma'am" using Brown and Levinson's Politeness Theory (1987) integrated with the perspective of Islamic Moral Mysticism (Akhlak Tasawuf). A descriptive qualitative method was employed, with data collected through reading and noting techniques and purposive sampling. The primary data source consists of 15 utterances drawn from dialogues between the two main characters, Mrs. Luella Bates Washington Jones and Roger, analyzed using the Miles, Huberman, and Saldaña (2014) model. The findings identify three politeness strategies: positive politeness (53.3%), negative politeness (26.7%), and bald on record (20%), while the off-record strategy was absent. Positive politeness emerged as the dominant strategy, reflecting the characters' efforts to build solidarity and moral transformation. Concurrently, the Akhlak Tasawuf analysis identified three prevailing values—tawadhu' (humility), shiddiq (truthfulness and sincerity), and hifdzul lisan (guarding one's speech)—each correlating with the politeness strategies employed. These findings suggest that linguistic politeness in this short story functions not merely as a pragmatic face-management tool, but also as a representation of ethical and spiritual values that foster behavioral change and the restoration of interpersonal relationships.